Answer:
n = 2
Explanation:
Simplifying
(n + 8) + (n + -12) = 0
Reorder the terms:
(8 + n) + (n + -12) = 0
Remove parenthesis around (8 + n)
8 + n + (n + -12) = 0
Reorder the terms:
8 + n + (-12 + n) = 0
Remove parenthesis around (-12 + n)
8 + n + -12 + n = 0
Reorder the terms:
8 + -12 + n + n = 0
Combine like terms: 8 + -12 = -4
-4 + n + n = 0
Combine like terms: n + n = 2n
-4 + 2n = 0
Solving
-4 + 2n = 0
Solving for variable 'n'.
Move all terms containing n to the left, all other terms to the right.
Add '4' to each side of the equation.
-4 + 4 + 2n = 0 + 4
Combine like terms: -4 + 4 = 0
0 + 2n = 0 + 4
2n = 0 + 4
Combine like terms: 0 + 4 = 4
2n = 4
Divide each side by '2'.
n = 2
Simplifying
n = 2